Approximation Algorithm for Max-Bisection Problem with the Positive Semidefinite Relaxation (Journal of Computational Mathematics, 2003)
Using outward rotations, we obtain an approximation algorithm for Max-Bisection problem, i.e., partitioning the vertices of an undirected graph into two blocks of equal cardinality so as to maximize the weights of crossing edges. In many interesting cases, the algorithm performs better than the algorithms of Ye and of Halperin and Zwick. The main tool used to obtain this result is semidefinite programming.
Keywords: Approximation algorithm; Max-Bisection problem; Semidefinite programming; Approximation ratio.